PENERAPAN QR-CODE DALAM PROSES PEMBAYARAN DIGITAL DI KAMPUS - Mohamad Arif Suryawan; La Ode Muhammad Jihad Al Faris (Prodi Teknik Informatika Unidayan Baubau, 2022)
The payment system at Dayanu Ikhsanuddin University (Unidayan) is done manually by taking a payment slip at the financial counter, then making payments at the designated bank, such as payment of tuition fees, KKN, graduation, PBL, PPL, and final project or thesis. Payment methods like this make students often experience difficulties in making payments, causing discomfort and tend to delay payments. This study aims to apply the QR Code system in the digital payment process on campus. The research method used is the waterfall model. The method implements a sequential software life flow, starting from analysis, design, coding, and testing. This research produces a digital payment application on the Unidayan campus by implementing a QR Code system which can later make it easier for students to make payments by making a top-up and then scanning the QR code. thus it can help the finance department get data on students who have or have not paid tuition fees, namely SPP, KKN, Graduation, PBL, and Final Projects or Thesis.